2007
DOI: 10.1002/mrd.20713
|View full text |Cite
|
Sign up to set email alerts
|

Immunoneutralization of endometrial monoclonal nonspecific suppressor factor beta (MNSFβ) inhibits mouse embryo implantation in vivo

Abstract: Successful embryo implantation and pregnancy in mammals depends on the establishment of immune tolerance between the maternal immune system and fetal cells. Monoclonal nonspecific suppressor factor beta (MNSFbeta), a cytokine produced by suppressor T cells in various tissues, possesses an antigen-nonspecific immune-suppressive function, and may be involved in the regulation of the uterine immune response during embryo implantation. In this study, anti-MNSFbeta IgG administered directly into the uterine lumen, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 38 publications
2
15
0
Order By: Relevance
“…This study demonstrates a stimulatory effect of MNSFβ on the secretion of IL-4 from mouse lymphocytes, as well as an inhibitory effect on their secretion of TNFα. Moreover, the results of the in vitro experiments using coculture model of mouse embryo and endometrial stromal cells to mimic embryo implantation in mice also showed that anti-MNSFβ antibody significantly inhibited embryo implantation (specifically hatching from the zona pellucida), consistent with and further defining the results of the in vivo experiments we previously reported [12].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This study demonstrates a stimulatory effect of MNSFβ on the secretion of IL-4 from mouse lymphocytes, as well as an inhibitory effect on their secretion of TNFα. Moreover, the results of the in vitro experiments using coculture model of mouse embryo and endometrial stromal cells to mimic embryo implantation in mice also showed that anti-MNSFβ antibody significantly inhibited embryo implantation (specifically hatching from the zona pellucida), consistent with and further defining the results of the in vivo experiments we previously reported [12].…”
Section: Discussionsupporting
confidence: 87%
“…The rabbit anti-mouse MNSFβ polyclonal antibody was prepared and its specificity previously demonstrated in our laboratory [12]. To detect the MNSFβ protein expression levels in transfected HCC-94 cells, 150 μL of protein lysis buffer (Beijing ComWin Biotech Co., Ltd., China) was added to each well.…”
Section: Detection Of Mnsfβ Protein Levels Expressed By Transfected Hmentioning
confidence: 99%
See 1 more Smart Citation
“…MNSF-β is an antigen nonspecific immune-suppressive cytokine produced by suppressor T cells, whose critical role during the embryo implantation has been shown in a murine model. 106 Blocking MNSF-β has even been proposed as a target for postcoital contraceptive drug. 107 A human ortholog of MNSF, human nonspecific suppressor factor, has been detected in ascitic fluid of patients with systemic lupus, 108 suggesting its role also in immune system regulation disorders leading to immune disease.…”
Section: Cytokinesmentioning
confidence: 99%
“…Expression levels remain low as implantation advances (Nie et al, 2000). Administration of antisera to FAU into the mouse uterine lumen inhibits implantation in a dosedependent manner (Wang et al, 2007), suggesting an essential role for secreted products in implantation. Trophoblast-derived interferons have been shown to induce endometrial FAU expression in pigs (Chwetzoff and d'Andrea, 1997), also supporting an important role for FAU in early pregnancy.…”
Section: Reproduction (Implantation)mentioning
confidence: 99%